Pengaruh Pemberian Sari Jangklong dan Parijoto terhadap Sifat Fisik, Mikrobiologi dan Kimia Yogurt Sinbiotik - Septiani Septiani; Fariza Yulia Kartika Sari; Susi Nurohmi (Media Gizi Kesmas, 2026)
Background: Local food production with natural bioactive compounds such as probiotics and prebiotics. Both of them called with a synbiotic product, which is essential for maintaining gut microbiota balance. The inulin in jangklong can support the growth of lactid acid bacteria, while parijoto contributes to the distinct taste and flavor. Objectives: This research aimed to determine the physical characteristics, total lactid acid bacteria, and inulin content of yogurt synbiotic from jangklong and parijoto. Methods: The research design used a Completely Randomized Design (CRD) with a single-factor treatment. Jangklong and parijoto juice were used in the study. Three experimental formulations (F1, F2, and F3) were assessed, containing 10%, 20%, and 30% jangklong, respectively, and a constant addition of 0.5% parijoto juice. Results: The results showed that the synbiotic yogurt added with jangklong and parijoto juice significantly affected pH, viscosity, and inulin (p<0.05), but total lactid acid bacteria counts did not differ. The yogurt’s physical characteristics included a pH range of 4.17–4.19 and a viscosity range of 1100–1500 cP. F3 had the highest lactid acid bacteria count (45x105 CFU/ml on day 2), and inulin content varied from 9.6% to 26.1%. Inulin content generally encouraged the growth of lactic acid bacteria, but this effect was not statistically significant. Conclusion: Physical characteristics of the pH and viscosity are in accordance with the SNI yogurt 01.2981:2009 standard, while the overall number of lactic acid bacteria remains below the SNI. Inulin levels differed significantly across the formulas.